1984
DOI: 10.1212/wnl.34.7.953
|View full text |Cite
|
Sign up to set email alerts
|

Miller Fisher syndrome

Abstract: Clinical and electrophysiologic data recorded in patients with Fisher syndrome characterized by ophthalmoplegia, ataxia, and areflexia are presented. Cases with limb weakness or pleocytosis in the CSF were excluded, according to Fisher. Ten patients were selected. All had hand and foot numbness. A large amount of protein without cell reaction was found during the third week of illness in serial CSF examinations. EMGs showed very slight limb involvement without spontaneous activity, and in most cases, facial mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
2
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 0 publications
6
35
2
2
Order By: Relevance
“…These findings suggest a block of conduction in the spinal roots, limb girdle plexuses or proximal segments of the nerves. Several reports had the consensus that sensory changes predominated with significant loss of amplitudes and mild motor and sensory conduction slowing [21, 22, 25, 26, 29]. In our study, this phenomenon was not observed.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…These findings suggest a block of conduction in the spinal roots, limb girdle plexuses or proximal segments of the nerves. Several reports had the consensus that sensory changes predominated with significant loss of amplitudes and mild motor and sensory conduction slowing [21, 22, 25, 26, 29]. In our study, this phenomenon was not observed.…”
Section: Discussioncontrasting
confidence: 43%
“…The results have been controversial. Although some studies revealed no evidence of affection of the peripheral nerves [9, 11, 12, 13], most studies revealed peripheral nerve involvement such as abnormalities in distal motor latencies, motor conduction velocities, sensory conduction velocities, F wave latencies and H reflexes [19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34]. Three out of our 10 patients had abnormal electrophysiological findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MFS is seen in two patients who had ataxia, areflexia, and ophthalmoplegia affecting 3, 4, and 6 cranial nerve. (10) The Polyneuropathy of Diphtheria Mimics GB Syndrome. However, there are few differences.…”
Section: Localization Of Lesion In the Nervesmentioning
confidence: 99%
“…In contrast, sensory nerve conduction studies (SNCSs) show decreased amplitudes of sensory nerve action potentials (SNAPs) in 70-90% of Caucasian patients with FS (8)(9)(10). Earlier reports from a small M none dysesthesia present none none positive day 10 2 28 M URI ataxia present none none negative day 7 3 23 M diarrhea diplopia absent none none not done day 16 4 68 M URI diplopia present none none positive day 17 5 36 F URI diplopia absent none none positive day 4 6 34 M diarrhea diplopia present none none positive day 4 hypesthesia group (group H, n = 4) 7 38 M URI diplopia present hypesthesia none negative day 11 8 21 F none diplopia present hypesthesia none positive day 5 9 38 F URI diplopia present hypesthesia hypesthesia positive day 14 10 68 M URI ataxia present hypesthesia hypesthesia positive day 4 The patients were divided into the following Two groups: those without hypesthesia (cases 1-6) and those with hypesthesia (cases 7-10).…”
Section: Introductionmentioning
confidence: 99%